The Training of Educational Researchers: Quality or Marketing in Higher Education? - Luis Alan Acuña Gamboa; Leticia Pons Bonals (Universidad Autónoma de Madrid, 2019)
Since the end of the twentieth century, higher education has been structuring and aligning itself more and more with global economic dynamics and interests, to the extent of subjecting its objectives to the visions, purposes and demands of the neoliberal capitalist economic structure that dominates the planet. Derived from this logic, there are two trends that are contradictory. On the one hand, Higher Education Institutions (IES), especially in the case of private initiative, find the possibility of offering programs that are subject to market laws without major quality controls, which also has the effect of facilitate and devalue the achievement of academic degrees; while, on the other hand, the political discourse assumes a commitment to raise the quality of education to have the human resources required by the country's development, imposing strict guidelines on educational programs to reach the standards that ensure said quality, same which, in the case of public ies, above all, are tied to access to increasingly scarce economic resources.